1937
DOI: 10.1515/bchm2.1937.250.4-6.262
|View full text |Cite
|
Sign up to set email alerts
|

Citronensäure im Gewebsstoffwechsel

Abstract: Der Abbau und die Funktion der Citronensäure waren bis vor kurzem dunkel, da der Neef und K ei ehe l 1 ) aufgezeigte Abbau zu Acetondicarbonsäure (/2-Ketoglutarsäure) nur ein untergeordneter Nebenabbau der Citronensäure sein kann, weil reine Acetondicarbonsäure im Atmungsversuch nicht als Donator wirkt [Wagner-Jauregg 2 )].Erst vor kurzem ist durch neue Arbeiten von Knoop und Martius 3 ' 4 ' 5 ) gezeigt worden, daß der Abbau der Citronensäure in der Hauptsache nicht über die /?-Ketoglutarsäure, sondern über di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1939
1939
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Knoop and Martins (38,48) and Martins (46) have shown that citric acid may arise through the condensation of pyruvic with oxaloacetic acid and subsequent oxidation, and that citric acid can be converted mto a;-ketoglutaric acid by an enzyme system in liver tissue, the intermediates probably being the well-known constituents of certain plants, aconitic and isocitric acids. Krebs (42) has confirmed this observation, as has also Breusch (18). The respiration of liver tissue was found to be stimulated to almost exactly the same extent by citric acid, cisaconitic acid, isocitric acid, and a-ketoglutaric acid.…”
Section: The Carbohydrate-organic Acid Metabolismmentioning
confidence: 65%
“…Knoop and Martins (38,48) and Martins (46) have shown that citric acid may arise through the condensation of pyruvic with oxaloacetic acid and subsequent oxidation, and that citric acid can be converted mto a;-ketoglutaric acid by an enzyme system in liver tissue, the intermediates probably being the well-known constituents of certain plants, aconitic and isocitric acids. Krebs (42) has confirmed this observation, as has also Breusch (18). The respiration of liver tissue was found to be stimulated to almost exactly the same extent by citric acid, cisaconitic acid, isocitric acid, and a-ketoglutaric acid.…”
Section: The Carbohydrate-organic Acid Metabolismmentioning
confidence: 65%
“…Ironically, Krebs himself was proving his theory on the cycle by fighting opposing views of other researchers who ignored the reversibility of several steps. Below is an excerpt from a reply to the criticisms of F. L. Breusch and of J. Thomas (Breusch, ; Thomas, ):
Several of the criticisms arise solely from a misinterpretation of the theory. Thomas as well as Breusch draw incorrect conclusions from the theory and argue against the theory when these conclusions are not confirmed by their experiments.
…”
Section: A Naïve Look At the Citric Acid Cyclementioning
confidence: 99%
“…This was the most convincing demonstration yet that the isomerization of the tricarboxylic acidsscitrate, cisaconitate, and isocitrateswas catalyzed by an enzyme different from that which carried out the oxidative decarboxylation of isocitrate to R-ketoglutarate. The name aconitase was proposed 2 and generally accepted for this enzyme (citrate (isocitrate) hydro-lyase, EC 4.2.1.3). The reactions catalyzed by aconitase are shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%